Ethnohistoire et marxisme: étude d'une région périphérique de l'empire Aztèque - Beaucage, Pierre (Anthropologica, 2022)
This article is divided into two sections. The first one presents a discussion of the Asiatic or Tributary Mode of Production, in the light of the more recent contributions to the marxian theory. The second applies this concept to the study of the Aztec Empire. This Empire constituted a social formation comprising many articulated modes of production: in the center of the Empire (Mexico Valley) the ecological conditions allowed the full development of the tributary mode of production while at the periphery the social formations were constituted of various types of village structures, more or less integrated into a hierarchy, according to the environment and the history of the region.